Development of fuzzy controller for maintaining temperature component of comfortable microclimate - Степанець, Олександр Васильович; Каракой, Андрій Вікторович (Technology audit and production reserves, 2016)
The prospects of controllers based on fuzzy logic for maintaining the temperature component of systems for climate control in buildings and the results of research in this area are discussed in the article. The main aim of the research is developing automatic controller of temperature microclimate condition on the basis of technology of fuzzy sets, providing minimal overshoot and the transition process in the task of stabilizing the temperature. Using this method can reduce the overshoot of controlled parameters of ventilation systems, reduce their identification time and increase the robustness of the controller in the presence of incomplete information about the object control compared to regular algorithms. Ways to optimize the control system for maintaining the set quality parameters are outlined. It is proposed to use the controller based on fuzzy logic for air conditioning systems, in which there are uncontrollable external disturbances and there is incomplete information about the object of control. Research results can be applied by expert designers of automatic control systems involved in automation, the stages of development and control algorithms during commissioning works to reduce system setup time.